Analysis of the Effect of Asset Allocation on Portfolio Performance with Diversification as an Intervening Variable - Dipa Teruna Awaludin; Hasanudin; Faysal Deni Rahman (International Journal of Science and Society, 2021)
This study aims to analyze the effect of asset allocation on portfolio performance with diversification as an intervening variable in the Pension Fund, a non-bank financial institution that manages the pension program and is registered and supervised by the Financial Services Authority (OJK) in the 2016-2019 period. A total of 34 Pension Funds were sampled so that the total sample was 136 in the 2016-2019 period. Data analysis using Structural Equation Modeling (SEM). The results showed that Selection Ability and Fund Size had a significant effect on Diversification, while Timing Ability had a significant effect on Portfolio Performance. Intervening test using Sobel Test shows that Diversification has not been able to mediate Asset Allocation on Portfolio Performance.